Disturbing Bones: from Grave-Violation to Exaltation of the Relic - Lappin, Anthony John (Mirator, 2018)
Starting from the sparse indications of the translation of relics in the Classical period and amongst pre-Constantinian Christians, we trace how the imperial family had a distinctive impact upon the practice and early popularity of translation, and show how, in its earliest phases, the conscious impiety of removing a body from its resting place was primarily, if not wholly, an Arian concern. Subsequent translations, beginning with Ambrose, show the episcopate re-affirming its authority over and against the emperors, culminating in Paschal II’s massive translation of relics within Rome in order to offer a centre of resistance to the revitalized iconoclasm of the Byzantine rulers.